The work of classroom assistants in special and mainstream education in Finland - Takala, Marjatta (British Journal of Special Education, 2007)
The contribution of teaching assistants, learning support assistants or classroom assistants is becoming increasingly important in inclusive and specialist classrooms. In this article, Marjatta Takala, professor in special education at the University of Helsinki, describes her research into the work of 14 classroom assistants working in a mix of mainstream and special schools in Helsinki, Finland. The results reveal that the tasks undertaken by assistants are different in mainstream and specialist settings and vary also according to the ages of the children involved. The assistants spent more of their time, for example, working directly with children if they worked in mainstream schools. Assistants in special schools, by comparison, spent more time assisting the teacher. Further, assistants working among older children spent more time waiting or simply listening to the lesson than those working with younger children, who seemed to be more actively involved with supporting learning. Marjatta Takala analyses her results by the full range of tasks encountered; according to three broad types of work; and in terms of the planning and co-operation undertaken by assistants and teachers at the class level. Her discussion will be of interest to anyone concerned with the development of support in the classroom and the education of both teachers and teaching assistants.